A Financial Performance Analysis On Pharmaceutical Companies With Reference To Nse - Mahalakshmi, S.; Ganesan, Dr. M. (Metallurgical and Materials Engineering, 2025)
The pharmaceutical industry plays a critical role in ensuring public health while also contributing significantly to economic growth and employment in India. As one of the core sectors listed on the National Stock Exchange (NSE), the financial health of pharmaceutical companies is vital not only for stakeholders but also for long-term national development. This study, titled "A Financial Performance Analysis on Pharmaceutical Companies with Reference to NSE," provides a comprehensive evaluation of selected leading pharma companies — Cipla, Sun Pharma, and Dr. Reddy’s — through detailed financial ratio analysis, correlation assessment, and factor analysis. The research spans five financial years (2019–2024) and assesses key performance indicators such as liquidity, profitability, earnings retention, and valuation metrics. The study applies analytical techniques including Kaiser-Meyer-Olkin (KMO) testing, Bartlett’s test, and factor loading to determine the most influential financial variables driving performance. The findings reveal that while Dr. Reddy’s consistently shows strong profitability and dividend distribution, Sun Pharma exhibits a comparatively weaker liquidity position. Cipla, on the other hand, maintains stable financial metrics with notable improvements in quick and current ratios. The results also show declining enterprise values and profit margins across all firms, suggesting the need for strategic financial restructuring. The research emphasizes the importance of liquidity optimization, inventory efficiency, and balanced reinvestment strategies to enhance financial resilience. The outcomes of this study will be valuable for corporate managers, investors, analysts, and policymakers seeking insights into the financial appraisal and long-term sustainability of India’s pharmaceutical sector.